Multifunctionality in neglected and underutilized crop species - Esquivel-Marín, Nancy (2024)
Neglected and underutilized crop species (NUS) are not widely grown or marketed. Certain crop types (amaranth, buckwheat, and quinoa) have advantages over commercial crops (rice, maize, and wheat). They can grow in harsh environments because of their greater resistance to abiotic and biotic stresses. Harnessing the NUS can solve global problems such as climate change, loss of agrobiodiversity, food insecurity, poverty, and unemployment in rural regions. Hence, this review investigates the various social, environmental, and economic functions associated with NUS cultivation to encourage and support future research on these crops.